Biosynthesis of AgNPs Mediated by Equisetum debile Roxb. Herb Water Extract and Its Potency as an Antioxidant - Retnaningtyas, Yuni; Karmilasari, Alviani Dwi; Puspitasari, Endah (Pharmaceutical Sciences and Research, 2024)
Silver nanoparticles (AgNPs) are metal nanoparticles currently under development. AgNPs are recognized for their remarkable stability, low reactivity, and advantageous biological properties, including antioxidant activity. Phenolic compounds derived from the Equisetum debile Roxb. (Ed-R) herb have the potential to be explored as bio-reduction and capping agents in the synthesis of silver nanoparticles. The primary objective of this study is to synthesize AgNPs using a water extract from Ed-R herb and to assess their antioxidant activity. The optimal composition for the biosynthesis of AgNPs comprises 10% Ed-R water extract, 8.0 mM AgNO3, and deionized water in a ratio of 0.5:20:12 (v/v/v), with the mixture incubated for 60 minutes at 50°C. AgNPs were characterized by conducted using UV-Vis Spectrophotometry, FT-IR, Scanning SEM, and PSA. The total phenolic content (TPC) of the Ed-R herb water extract at the optimal concentration (10%) was determined to be 61.503 ± 0.089 mg GAE 100 mL-1. The characterization results indicated that the AgNPs exhibited a spherical morphology, with a particle size of 67 nm, a polydispersity index (PDI) of 0.424, a maximum wavelength of 423 nm, and an absorbance value of 1.397. The antioxidant activity of AgNPs was evaluated using the DPPH method, resulting in an IC50 value of 76.604 ± 0.846 μg mL-1, which signifies strong antioxidant activity. These findings suggest that the water extract from the Ed-R herb can effectively act as both bioreduction and capping agent in the synthesis of AgNPs, which demonstrates significant antioxidant properties.